Mild cognitive impairment in mild brain injury (MBI) patients: An event related potential (ERP) and neuropsychology study. (Bangladesh Journal of Medical Science, 2019)
Objectives: To evaluate auditory cognitive function in mild brain injury (MBI) patients, which is important to determine for rehabilitation and improve quality of their life.Methods: Participants (n=19/group) were divided into group 1 (G1-control), group 2 (G2/1st test-MBI/within 7 days of road traffic accident-RTA) and group 3 (G3/2nd test-MBI/2-6 months after RTA). Event related potentials (ERPs) were conducted using a 128-sensor net; participants counted silently rare target tone stimuli and ignored standard tones. Several neuropsychology tests like Verbal fluency test (PAS), Wisconsin Card Sorting Test (WCST), Rey Auditory Verbal and Learning Test (RAVLTIM, RAVLTDR and RAVLTTS) and Beck Depression Inventory (BDI) were subsequently administered.Results: Sensory (P50, N100) and cognitive (P300) ERP components were analysed from ERP waveforms. There were no significant group differences in amplitudes or latencies for all components across sites except P300 component amplitudes at T6 location. P50, N100 and P300 ERP components exhibited non-significantly increased amplitudes in G2 and G3 compared with G1 at all sites; non-significantly shorter latencies were identified at various sites. At several locations, G3 evoked non-significantly increased amplitudes and longer latencies with shorter latencies to other sites compared with G2 in all components. The MBI (G3) group exhibited significantly increased WCST, RAVLTIM and RAVLTDR scores compared with G1.Conclusion: These findings indicate MBI patients may have mild auditory, cognitive and executive dysfunctions with good auditory memory. MBI was associated with mild depression.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.557-566